Growth Arrest Specific 6 Concentration is Increased in the Cerebrospinal Fluid of Patients with Alzheimer's Disease. - Sainaghi, Pier Paolo; Bellan, Mattia; Lombino, Franco; Alciato, Federica; Carecchio, Miryam; Galimberti, Daniela; Fenoglio, Chiara; Scarpini, Elio; Cantello, Roberto; Pirisi, Mario; Comi, Cristoforo (J Alzheimers Dis, 2017)
Growth arrest specific 6 (Gas6) has neurotrophic and neuroinflammatory functions, and may play a role in Alzheimer's disease (AD). In keeping with this hypothesis, we observed that cerebrospinal fluid (CSF) Gas6 is increased in AD patients compared to controls (63 versus 67 subjects; median value 13.3 versus 9.1 ng/ml; p < 0.0001). Thereafter, we assessed whether CSF Gas6 concentration was correlated to the following parameters: disease duration, MMSE score two years after clinical diagnosis, AD CSF biomarkers, and years of formal schooling. We detected an inverse correlation between CSF Gas6 levels at diagnosis and both disease duration (p < 0.0001) and decrease in the MMSE score two years later (p < 0.0001). Conversely, we found no correlation between CSF Gas6 and both AD biomarkers and years of formal schooling. In conclusion, our results suggest that upregulation of CSF Gas6 may be part of a defensive response aimed at counteracting AD progression.